Mouse model carrying H222P-Lmna mutation develops muscular dystrophy and dilated cardiomyopathy similar to human striated muscle laminopathies - Arimura, Takuro; Helbling-Leclerc, Anne; Massart, Catherine; Varnous, Shaida; Niel, Florence; Lacène, Emmanuelle; Fromes, Yves; Toussaint, Marcel; Mura, Anne-Marie; Keller, Dagmar I.; Amthor, Helge; Isnard, Richard; et al. (Human molecular genetics, 2005)
Laminopathies are a group of disorders caused by mutations in the LMNA gene encoding A-type lamins, components of the nuclear lamina. Three of these disorders affect specifically the skeletal and/or cardiac muscles, and their pathogenic mechanisms are still unknown. We chose the LMNA H222P missense mutation identified in a family with autosomal dominant Emery–Dreifuss muscular dystrophy, one of the striated muscle-specific laminopathies, to create a faithful mouse model of this type of laminopathy. The mutant mice exhibit overtly normal embryonic development and sexual maturity. At adulthood, male homozygous mice display reduced locomotion activity with abnormal stiff walking posture and all of them die by 9 months of age. As for cardiac phenotype, they develop chamber dilation and hypokinesia with conduction defects. These abnormal skeletal and cardiac features were also observed in the female homozygous mice but with a later-onset than in males. Histopathological analysis of the mice revealed muscle degeneration with fibrosis associated with dislocation of heterochromatin and activation of Smad signalling in heart and skeletal muscles. These results demonstrate that LmnaH222P/H222P mice represent a good model for studying laminopathies affecting striated muscles as they develop a dystrophic condition of both skeletal and cardiac muscles similar to the human diseases.